Application of the Contextual Teaching and Learning (CTL) Learning Model to Social Studies Learning Outcomes in Grade IV Students - Ariyani, Farida; Frima, Aren; Firduansyah, Dedy (Global Education Journal, 2025)
In the world of education, Social Sciences (IPS) is one of the important aspects that need to be taught to students. This study aims to determine the completeness of social studies learning outcomes after applying the Contextual Teaching and Learning (CTL) learning model to social studies learning for grade IV students of SD Negeri 2 Trikarya. The method used in this study is quantitative with a quasi-experimental approach. In this study, 1 sample class was used, namely class IV with a total of 28 students. This means that all members of the population are sampled, the sampling technique is carried out with saturated sampling techniques. The instrument used in this study was in the form of multiple-choice questions totaling 15 questions. Data collection is carried out using tests. Data were analyzed using the z-test formula. The results of the study showed that based on the results of the data analysis test with a confidence level of α = 5%, it showed that Zcal > Ztabel (9.09) > (1.64) this means that HO was rejected and Ha was accepted. So, the conclusion is that the learning outcomes of social studies class IV SD Negeri 2 Trikarya after the implementation of the CTL learning model are significantly complete.